Advanced frequency-domain compensator design for subsystems within a nuclear generating station. (October 2021) - Tacke, Jonathan; Borrelli, R.A.; Roberson, Dakota
Abstract: Like all electrical generating stations, nuclear plants possess many feedback structures. Application of frequency-domain control design techniques has the potential to improve the performance of these feedback systems, thus improving the overall resiliency of the generating station and the grid at large. Typically the applicability of such design techniques are limited by the availability of detailed plant descriptions. In this work, an analysis is performed of several control structures of a nuclear generating station from a frequency-domain control perspective. The model used is that of a training simulator for reactor operators. The applicability of high performance control techniques to a number of subsystems is assessed and compensators are developed for the most promising systems. In recent years there has been renewed work in the application of classical control techniques to systems where the plant model is not fully known. One such technique is the Cloud technique, which is used to develop a type of controller known as a Modified Bode Optimal (MBO) controller. This technique is applied to develop large feedback compensators for two control systems within a simulated nuclear generating station. The relative performance of these systems is assessed using traditional time-domain metrics. Highlights: Frequency-domain control is applicable to a wider range of systems than ever before. NPPs can be improved with the use high-performance control techniques. A novel control design can be developed for complex systems using a simple technique. Using MBO compensators for AVR and TCS improve system performance considerably.